Techno‐economic analysis of the use of atomic layer deposited transition metal oxides in silicon heterojunction solar cells. (11th March 2022) - Chang, Nathan L.; Poduval, Geedhika K.; Sang, Borong; Khoo, Kean; Woodhouse, Michael; Qi, Fred; Dehghanimadvar, Mohammad; Li, Wei Min; Egan, Renate J.; Hoex, Bram
Abstract: The industry for producing silicon solar cells and modules has grown remarkably over the past decades, with more than a 100‐fold reduction in price over the past 45 years. The main solar cell fabrication technology has shifted over that time and is currently dominated by the passivated emitter and rear cell (PERC). Other technologies are expected to increase in market share, including tunnel‐oxide passivated contact (TOPCon) and heterojunction technology (HJT). In this paper, we examine the cost potential for using atomic layer deposition (ALD) to form transition metal oxide (TMO) layers ( MoO x, TiO x and aluminium‐doped zinc oxide [AZO]) to use as lower cost alternatives of the p‐doped, n‐doped and indium tin oxide (ITO) layers, respectively, the layers normally used in HJT solar cells. Using a bottom‐up cost and uncertainty model with equipment cost data and process experience in the lab, we find that the production cost of these variations will likely be lower per wafer than standard HJT, with the main cost drivers being the cost of the ALD precursors at high‐volume production. We then considered what efficiency is required for these sequences to be cost effective in /W and discuss whether these targets are technically feasible. This work motivates further work in developing these ALD TMO processes to increase their efficiency towards their theoretical limits to take advantage of the processing cost advantage. Abstract : Bottom‐up cost assessment of using atomic layer deposited (ALD) transition metal oxide (TMO) layers in silicon heterojunction (HJT) solar cells is presented. MoOx, TiOx and AZO are potentially lower manufacturing cost (/cell) than the standard doped a‐Si and ITO layers used in HJT solar cells; key cost uncertainty is volume pricing of ALD precursors. For each ALD TMO layer, cost and efficiency requirements are identified for commercial competitiveness (/W), and compared with theoretical limits—this provides targets for R&D efforts.